Prove that \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Answer
Verified
463.5k+ views
Hint: We start solving the problem by considering the L.H.S (Left hand side) of the given proof and substituting $\dfrac{1}{\tan \theta }=\cot \theta $ and $\dfrac{1}{\cot \theta }=\tan \theta $ in it. We then make use of the trigonometric identities $\left( 1+{{\cot }^{2}}\theta \right)={{\operatorname{cosec}}^{2}}\theta $ and $\left( 1+{{\tan }^{2}}\theta \right)={{\sec }^{2}}\theta $ to proceed through the problem. We then make use of the results $\sec \theta =\dfrac{1}{\cos \theta }$, $\operatorname{cosec}\theta =\dfrac{1}{\sin \theta }$ and ${{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $ to proceed further into the problem. We then make the necessary calculations to complete the required proof.
Complete step by step answer:
According to the problem, we need to prove the result \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Let us consider the L.H.S (Left Hand Side) and try to prove it equal to the R.H.S (Right Hand Side).
So, we have \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)\].
We know that $\dfrac{1}{\tan \theta }=\cot \theta $ and $\dfrac{1}{\cot \theta }=\tan \theta $. Let us substitute these results.
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( 1+{{\cot }^{2}}\theta \right)\left( 1+{{\tan }^{2}}\theta \right)\] ---(1).
We know that $\left( 1+{{\cot }^{2}}\theta \right)={{\operatorname{cosec}}^{2}}\theta $ and $\left( 1+{{\tan }^{2}}\theta \right)={{\sec }^{2}}\theta $. Let us substitute these results in equation (1).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( {{\operatorname{cosec}}^{2}}\theta \right)\left( {{\sec }^{2}}\theta \right)\] ---(2).
We know that $\sec \theta =\dfrac{1}{\cos \theta }$ and $\operatorname{cosec}\theta =\dfrac{1}{\sin \theta }$. Let us substitute these results in equation (2).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( \dfrac{1}{{{\sin }^{2}}\theta } \right)\left( \dfrac{1}{{{\cos }^{2}}\theta } \right)\].
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }\] ---(3).
We know that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1\Leftrightarrow {{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $. Let us substitute this result in equation (3).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta \left( 1-{{\sin }^{2}}\theta \right)}\].
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
So, we can see that L.H.S (Left hand side) is equal to R.H.S (Right Hand Side).
∴ We have proved the trigonometric result \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Note: We should perform each step carefully in order to complete the proof properly. We can also solve this problem as shown below:
We have \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)\] ---(4).
We know that $\tan \theta =\dfrac{\sin \theta }{\cos \theta }$ and $\cot \theta =\dfrac{\cos \theta }{\sin \theta }$. Let us substitute this results in equation (4).
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( 1+\dfrac{1}{\dfrac{{{\sin }^{2}}\theta }{{{\cos }^{2}}\theta }} \right)\left( 1+\dfrac{1}{\dfrac{{{\cos }^{2}}\theta }{{{\sin }^{2}}\theta }} \right)$.
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( 1+\dfrac{{{\cos }^{2}}\theta }{{{\sin }^{2}}\theta } \right)\left( 1+\dfrac{{{\sin }^{2}}\theta }{{{\cos }^{2}}\theta } \right)$.
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( \dfrac{{{\sin }^{2}}\theta +{{\cos }^{2}}\theta }{{{\sin }^{2}}\theta } \right)\left( \dfrac{{{\cos }^{2}}\theta +{{\sin }^{2}}\theta }{{{\cos }^{2}}\theta } \right)$ ---(5).
We know that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$. Let us substitute this in equation (5).
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( \dfrac{1}{{{\sin }^{2}}\theta } \right)\left( \dfrac{1}{{{\cos }^{2}}\theta } \right)$.
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }$ ---(6).
We know that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1\Leftrightarrow {{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $. Let us substitute this result in equation (6).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta \left( 1-{{\sin }^{2}}\theta \right)}\].
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Complete step by step answer:
According to the problem, we need to prove the result \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Let us consider the L.H.S (Left Hand Side) and try to prove it equal to the R.H.S (Right Hand Side).
So, we have \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)\].
We know that $\dfrac{1}{\tan \theta }=\cot \theta $ and $\dfrac{1}{\cot \theta }=\tan \theta $. Let us substitute these results.
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( 1+{{\cot }^{2}}\theta \right)\left( 1+{{\tan }^{2}}\theta \right)\] ---(1).
We know that $\left( 1+{{\cot }^{2}}\theta \right)={{\operatorname{cosec}}^{2}}\theta $ and $\left( 1+{{\tan }^{2}}\theta \right)={{\sec }^{2}}\theta $. Let us substitute these results in equation (1).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( {{\operatorname{cosec}}^{2}}\theta \right)\left( {{\sec }^{2}}\theta \right)\] ---(2).
We know that $\sec \theta =\dfrac{1}{\cos \theta }$ and $\operatorname{cosec}\theta =\dfrac{1}{\sin \theta }$. Let us substitute these results in equation (2).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( \dfrac{1}{{{\sin }^{2}}\theta } \right)\left( \dfrac{1}{{{\cos }^{2}}\theta } \right)\].
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }\] ---(3).
We know that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1\Leftrightarrow {{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $. Let us substitute this result in equation (3).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta \left( 1-{{\sin }^{2}}\theta \right)}\].
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
So, we can see that L.H.S (Left hand side) is equal to R.H.S (Right Hand Side).
∴ We have proved the trigonometric result \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Note: We should perform each step carefully in order to complete the proof properly. We can also solve this problem as shown below:
We have \[\left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)\] ---(4).
We know that $\tan \theta =\dfrac{\sin \theta }{\cos \theta }$ and $\cot \theta =\dfrac{\cos \theta }{\sin \theta }$. Let us substitute this results in equation (4).
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( 1+\dfrac{1}{\dfrac{{{\sin }^{2}}\theta }{{{\cos }^{2}}\theta }} \right)\left( 1+\dfrac{1}{\dfrac{{{\cos }^{2}}\theta }{{{\sin }^{2}}\theta }} \right)$.
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( 1+\dfrac{{{\cos }^{2}}\theta }{{{\sin }^{2}}\theta } \right)\left( 1+\dfrac{{{\sin }^{2}}\theta }{{{\cos }^{2}}\theta } \right)$.
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( \dfrac{{{\sin }^{2}}\theta +{{\cos }^{2}}\theta }{{{\sin }^{2}}\theta } \right)\left( \dfrac{{{\cos }^{2}}\theta +{{\sin }^{2}}\theta }{{{\cos }^{2}}\theta } \right)$ ---(5).
We know that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1$. Let us substitute this in equation (5).
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\left( \dfrac{1}{{{\sin }^{2}}\theta } \right)\left( \dfrac{1}{{{\cos }^{2}}\theta } \right)$.
$\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }$ ---(6).
We know that ${{\sin }^{2}}\theta +{{\cos }^{2}}\theta =1\Leftrightarrow {{\cos }^{2}}\theta =1-{{\sin }^{2}}\theta $. Let us substitute this result in equation (6).
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta \left( 1-{{\sin }^{2}}\theta \right)}\].
\[\Rightarrow \left( 1+\dfrac{1}{{{\tan }^{2}}\theta } \right)\left( 1+\dfrac{1}{{{\cot }^{2}}\theta } \right)=\dfrac{1}{{{\sin }^{2}}\theta -{{\sin }^{4}}\theta }\].
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE